A novel bioelectrochemical system designed to manage wastewater for simultaneous bioelectricity and hydrogen production - Goren, Aysegul Yagmur; Dincer, Ibrahim; Khalvati, Ali (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
Recently, there has been increasing interest in the simultaneous management of wastewaters for the sustainable supply of clean energy, hydrogen (H2), and water. In this regard, we designed and evaluated a co-integrated microbial electrolysis cell (MEC) and microbial fuel cell (MFC) hybrid system for simultaneous H2 production, wastewater treatment, and energy production in a single chamber. The effects of applied voltage, wastewater to inoculum ratio, temperature, and initial pH on H2 production performance of the MEC reactor are evaluated. Under improved conditions (applied voltage of 1.0 V, wastewater-to-activated sludge ratio of 1:2, temperature of 35 degrees C, and initial pH of 7.0), the highest H2 production rate in the MEC system is found as 26.5 mL/L. day In the MFC reactor, the maximum voltage of 215 mV with a power density of 4.66 W/m3 and a COD removal efficiency of 29.7 % is obtained at a temperature of 55 degrees C and cow manure to distilled water ratio of 2:1. Moreover, the co-integrated MEC-MFC system is operated under fed-batch operating mode and the H2 production at each cycle is obtained as 3.27-3.42 mL/L. day following fresh wastewater feeding. Consequently, these results show that co-integrated MEC-MFC systems for self-sustaining production of H2 and wastewater treatment become feasible, providing a potential route for converting organic-rich wastewater into H2 and as a sustainable energy source with waste management.
Keywords: Hydrogen production; Bioenergy; Microbial fuel cell; Microbial electrolysis cell; Sustainability; Wastewater; BIOHYDROGEN PRODUCTION; COUPLED SYSTEM; FERMENTATION; GENERATION; Agriculture; Biotechnology & Applied Microbiology; Energy & Fuels